Comparison of the Disposable Streamlined Liner of the Pharynx Airway and the Disposable I-gel in Anaesthetized, Paralyzed Adults: A Randomized Prospective Study - Khaled EL-Radaideh; Ala"a Alhowary; Diab Bani Hani (Anesthesiology Research and Practice)
Introduction. This study compared streamlined liner of the pharynx airway (SLIPA) and I-gel noninflatable, single-use, supraglottic airway device (SAD) performance in anesthetized, paralyzed adults. Methods. Eighty adults (ASA physical statuses I–III) who were undergoing elective procedures under general anesthesia with an SAD were enrolled in this prospective, randomized, single-blind study. Subjects were randomly and evenly assigned to the SLIPA or I-gel group for intraoperative airway management. Ease and number of insertions, insertion time, oropharyngeal sealing pressure, hemodynamic response, oxygen saturation (SpO2), end-tidal CO2 (EtCO2), and peri- and postoperative complications were examined. Results. The SLIPA and I-gel devices were successfully inserted in 100% and 95% of subjects, respectively. In two I-gel subjects (5%), ventilation was not possible after two attempts, but a size 55 SLIPA was successfully inserted in both cases. Forty-two and 38 patients were ultimately included in the SLIPA and I-gel groups, respectively. Insertion time was significantly shorter with the SLIPA (11.19±3.03 s) than with the I-gel (15.05±6.37 s, P=0.003). Oropharyngeal sealing pressure was significantly higher in SLIPA (28.76±3.11 cmH2O) than in I-gel (25.9±3.65 cmH2O) subjects (P=0.001). Blood staining occurred more frequently in SLIPA (n=8, 19.0%) than in I-gel (n=5, 13.2%) patients (P<0.01). Heart rate, mean arterial blood pressure, SpO2, and EtCO2 were not significantly different between groups. Conclusion. Although blood staining incidence was higher, SLIPA insertion was easier and faster than I-gel insertion. The SLIPA provided better airway sealing pressure. Both devices had similar mechanical ventilation and oxygenation characteristics and comparable hemodynamic stability. Both noninflatable SADs are useful, but SLIPA rapid insertion and good airway sealing make it an effective alternative to the I-gel.